1979
DOI: 10.1002/dev.420120207
|View full text |Cite
|
Sign up to set email alerts
|

Effects of rearing in different environments on subsequent environmental preference in rats

Abstract: Environmental preference of male rats reared during 2 months after weaning either in a complex and changing environment (EC) or in empty laboratory cages (SC) was assessed in 4 different experiments. For 2 weeks after differential rearing, rats were placed in groups of 6 in testing cages which were divided into 2 compartments with communicating holes. One of these compartments was empty; the other contained 6 objects (complex compartment). Daily, 3 objects were moved from 1 compartment to the other and replace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1979
1979
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…In a factorial analysis of initial experience condition by age of subject, the consistent presence of experience effects combined with the relatively rare appearance of either age effects or interactions indicated that the dominant result was for the dendritic effects of the initial superenriched environment exposure to persist through the subsequent period of individual housing.Although it has been known for some time that various regions of the neocortex exhibit altered dendritic morphology in response to exposure to a complex environment (Greenough & Volkmar, 1973), the degree to which these dendritic effects persist is unknown. Exposure of rodents to a complex environment (EC) also results in significant changes in behavior relative to animals housed individually (1C) or socially in standard caging (e.g., Hebb, 1947;Will, Pallaud, Ungerer, & Ropartz, 1979; see Greenough, 1976, for review), brain chemistry, and brain size and weight (e.g., Diamond, 1967;Rosenzweig, Bennett, & Diamond, 1972). The relative permanence of some of these environmentally induced changes has been examined by switching animals between the complex environment and individual housing.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In a factorial analysis of initial experience condition by age of subject, the consistent presence of experience effects combined with the relatively rare appearance of either age effects or interactions indicated that the dominant result was for the dendritic effects of the initial superenriched environment exposure to persist through the subsequent period of individual housing.Although it has been known for some time that various regions of the neocortex exhibit altered dendritic morphology in response to exposure to a complex environment (Greenough & Volkmar, 1973), the degree to which these dendritic effects persist is unknown. Exposure of rodents to a complex environment (EC) also results in significant changes in behavior relative to animals housed individually (1C) or socially in standard caging (e.g., Hebb, 1947;Will, Pallaud, Ungerer, & Ropartz, 1979; see Greenough, 1976, for review), brain chemistry, and brain size and weight (e.g., Diamond, 1967;Rosenzweig, Bennett, & Diamond, 1972). The relative permanence of some of these environmentally induced changes has been examined by switching animals between the complex environment and individual housing.…”
mentioning
confidence: 99%
“…Although it has been known for some time that various regions of the neocortex exhibit altered dendritic morphology in response to exposure to a complex environment (Greenough & Volkmar, 1973), the degree to which these dendritic effects persist is unknown. Exposure of rodents to a complex environment (EC) also results in significant changes in behavior relative to animals housed individually (IC) or socially in standard caging (e.g., Hebb, 1947; Will, Pallaud, Ungerer, & Ropartz, 1979; see Greenough, 1976, for review), brain chemistry, and brain size and weight (e.g., Diamond, 1967; Rosenzweig, Bennett, & Diamond, 1972). The relative permanence of some of these environmentally induced changes has been examined by switching animals between the complex environment and individual housing.…”
mentioning
confidence: 99%
“…We extracted details of which resources (substrates, items or structures) were included in both housing types. Further, we extracted data on factors likely to compromise EH effectiveness (determined a priori: see pre-registered protocol Additional file 3 ), hereafter referred to as ‘red flags’: those likely to inadvertently increase aggression (via resource guarding in group-housed male mice) [ 12 , 58 , 59 ], fear (caused by the frequent rotation of novel objects, or providing novel resources to old animals who may be neophobic) [ 60 , 61 ] or disinterest (possible in old animals, due to anhedonia) [ 21 ]. We also flagged any EH supplied for very short timeframes (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, rats were found to spend more time interacting with natural objects (rocks, sticks, dirt) as opposed to artificial objects (plastic toys) 41 , and spent more time interacting with objects in a cage containing multiple different objects of different types as opposed to multiple objects of the same type 42 . Yet, a preference for objects within the cage was not always observed, with one study finding that rats showed a preference for an empty compartment compared with a compartment containing six different objects (such as chains, ladders and blocks of wood) 43 .…”
Section: Refinements That Have Been Studied?mentioning
confidence: 99%